Iron-loaded deferiprone can support full hemoglobinization of cultured red blood cells - Gallego-Murillo, Joan Sebastián; Yağcı, Nurcan; Pinho, Eduardo Machado; Wahl, Sebastian Aljoscha; van den Akker, Emile; von Lindern, Marieke (Scientific Reports, 2023)
Iron, supplemented as iron-loaded transferrin (holotransferrin), is an essential nutrient in mammalian cell cultures, particularly for erythroid cultures. The high cost of human transferrin represents a challenge for large scale production of red blood cells (RBCs) and for cell therapies in general. We evaluated the use of deferiprone, a cell membrane-permeable drug for iron chelation therapy, as an iron carrier for erythroid cultures. Iron-loaded deferiprone (Def3·Fe3+, at 52 µmol/L) could eliminate the need for holotransferrin supplementation during in vitro expansion and differentiation of erythroblast cultures to produce large numbers of enucleated RBC. Only the first stage, when hematopoietic stem cells committed to erythroblasts, required holotransferrin supplementation. RBCs cultured in presence of Def3·Fe3+ or holotransferrin (1000 µg/mL) were similar with respect to differentiation kinetics, expression of cell-surface markers CD235a and CD49d, hemoglobin content, and oxygen association/dissociation. Replacement of holotransferrin supplementation by Def3·Fe3+ was also successful in cultures of myeloid cell lines (MOLM13, NB4, EOL1, K562, HL60, ML2). Thus, iron-loaded deferiprone can partially replace holotransferrin as a supplement in chemically defined cell culture medium. This holds promise for a significant decrease in medium cost and improved economic perspectives of the large scale production of red blood cells for transfusion purposes.
CRIS-Team Scopus Importer:2023-06-16